2010
DOI: 10.1186/1471-2172-11-20
|View full text |Cite
|
Sign up to set email alerts
|

GPR30, but not estrogen receptor-α, is crucial in the treatment of experimental autoimmune encephalomyelitis by oral ethinyl estradiol

Abstract: BackgroundRemission of multiple sclerosis during periods of high ovarian hormone secretion (such as pregnancy) has led to a great deal of interest in the potential for estrogens to treat autoimmune disease. Previous work has established that 17β-estradiol can inhibit onset of experimental autoimmune encephalomyelitis (EAE), while ethinyl estradiol (EE) can reduce the severity of established disease. In the current study, the influence of estrogen receptor-α (ERα) and the G-protein coupled estrogen receptor (GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 25 publications
1
53
0
1
Order By: Relevance
“…This difference in cytokine production may be an important contributor to the disease reduction seen in the high-/medium-dose estrogen mice. Increased IL-10 secretion is frequently associated with improvement in disease, while IL-10-deficient animals have a greater T-cell response to antigen and develop more severe EAE compared to WT mice (Yates et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This difference in cytokine production may be an important contributor to the disease reduction seen in the high-/medium-dose estrogen mice. Increased IL-10 secretion is frequently associated with improvement in disease, while IL-10-deficient animals have a greater T-cell response to antigen and develop more severe EAE compared to WT mice (Yates et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It exhibits an affinity for ERa/b approximately twofold better than E2 (Blair et al, 2000), but its affinity for GPER has not been reported. In the animal model of multiple sclerosis (EAE), E2 can prevent onset of disease but it cannot treat established disease, whereas EE can reduce the severity of existing disease (Yates et al, 2010). The protective effects of E2 have been reported to be reduced in both ERa knockout (Morales et al, 2006) as well as GPER knockout mice .…”
Section: Synthetic Steroid Derivatives Analogs and Therapeuticsmentioning
confidence: 99%
“…The protective effects of G-1 were absent in GPER knockout mice, confirming the selectivity of G-1 for GPER in vivo . Furthermore, the therapeutic efficacy of ethynyl estradiol in established disease required expression of GPER but not ERa and were associated with anti-inflammatory cytokine interleukin (IL)-10 production (Yates et al, 2010). Mechanistic studies revealed that G-1 not only enhanced the suppressive activity of CD4 + Foxp3 + T regulatory cells through upregulation of programmed death 1 ), but also inhibited inflammatory cytokine production by macrophages (Blasko et al, 2009), suggesting multiple coordinated or perhaps independent effects on the immune system.…”
Section: Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…All oestrogens are not exactly alike [5,23]. Importantly and unlike 17β-oestradiol, the common oestrogen found in pills ethynil oestradiol [24,25] and progesterone [26] reduce the clinical severity of EAE when given after the onset of disease signs. Because the large majority of our patients have used different combinations of ethynil oestradiol and a progestogen, we cannot exclude that these hormones could have different impacts on the observed protective effects.…”
Section: P-valuementioning
confidence: 99%